The Effect Of Early Chelıoplasty On The Maxıllary Alveolar Cleft Dımensıon In Infants Wıth Clefı Lıp And Palate - Servet Doğan (Galenos Yayinevi, 1990)
The authors are in agreement in the early treatment of cleft lippalate babies. But the time of thi chelioplasty is still controversial. In this present study, we applied chelioplasty in totally 26 cleft lip-palate babies by dividing them into two groups. The chelioplasty was applied in the first week after the birth in the first group, and after the application of the extraoral traction in the second group. We also compared the results between the 0. month and the 3 rd. month.